A Qualitative Analysis on the Role of Auditors in Preventing Financial Crises - Sapiri, Muhtar (Manunggal Halim Jaya, 2024)
This study investigates the pivotal role of auditors in mitigating risks associated with financial crises, focusing on risk assessment, internal control evaluation, and addressing complexities in financial instruments. Employing a qualitative research approach, data was gathered through comprehensive literature review and thematic analysis. Findings underscore auditors' significance as guardians of financial integrity, detecting errors, and fraud in financial statements, thus enhancing transparency and investor confidence. Moreover, auditors' assessment of internal controls aids in fraud prevention and compliance risk management, crucial for organizational resilience. Challenges in evaluating complex financial instruments highlight the need for specialized expertise and technological advancements. The study emphasizes interdisciplinary collaboration, continuous professional development, and adherence to ethical standards as essential strategies for auditors to navigate emerging risks effectively. Overall, the research contributes to understanding auditors' multifaceted role in preventing financial crises and underscores the importance of robust risk assessment practices in maintaining financial stability.